Neutrophil gelatinase-associated lipocalin is a urine-based biomarker for diagnosing active lupus nephritis - Anthony Chakma; Debatosh Paul; Sheuly Ferdoushi; Minhaj Rahim Choudhury; Md. Saiful Islam (Bangabandhu Sheikh Mujib Medical University Journal)
Background: Lupus nephritis is one of the most serious complications of systemic lupus erythematosus (SLE). Urinary neutrophil gelatinase-associated lipocalin (NGAL) is a non-invasive biomarker that may aid in diagnosing active lupus nephritis. This study seeks to evaluate NGAL as a urine-based biomarker to diagnose active lupus nephritis.